Content and workflow management for library web sites case studies - Yu Holly (Hershey Information Science, 2005)
It provides practical and applicable web content management solutions through case studies. It contains successful database-to-web applications as employed in a variety of academic libraries. The applications vary in scope and cover a range of practical
Keywords: Electronic information resource searching; Electronic reference services; Library web sites; Library web sites-design; Online databases